Structural changes in the lobar regions of brain in cerebral small-vessel disease patients with and without cognitive impairment: An MRI-based study with automated brain volumetry. Issue 126 (May 2020) - Liu, Chengxia; Zhao, Lei; Yang, Shiqi; Luo, Yishan; Zhu, Wenhao; Zhu, Wenzhen; Shi, Lin
Highlights: CSVD-MCI patients presented significant lobar atrophy of GM and WM. CSVD patients showed significant alterations of structural covariance. Alterations of structural covariance was mainly in bilateral cingulate and temporal lobes. Abstract: Purpose: This study aims to investigate the alterations of brain volumetry and associated structural covariance at lobar level in cerebral small-vessel disease (CSVD) with and without cognitive impairment. Method: Twenty-seven CSVD patients with mild cognitive impairment (CSVD-MCI), 37 CSVD patients with normal cognition (CSVD-NC), and 35 controls, underwent T1-weighted imaging of magnetic resonance. Volume of gray matter (GM) and white matter (WM) and a lobar atrophy index that measures the ratio of cerebrospinal fluid to brain parenchyma were quantified for each lobe. One-way ANOVA with multiple comparison corrections was performed to compare these volumetric measures. Volumetric structural covariance analyses were performed with lobar atrophy indexes to investigate the alterations of anatomical covariance within each pair of lobar regions in CSVD-NC and CSVD-MCI subjects compared with controls. Results: CSVD-NC subjects presented no significant volumetric differences with controls in any of the lobar regions. Compared with controls, CSVD-MCI patients presented significantly smaller volume of GM in bilateral frontal and parietal lobes, significantly smaller volume of WM in right cingulate lobe, and significantly larger lobar atrophy indexes of bilateral temporal, insular lobes and left cingulate lobe ( P < 0.05). Both CSVD-NC group and CSVD-MCI group showed significant differences of structural covariance as measured by lobar atrophy index compared with controls. In particular, CSVD-MCI group showed even more extensive alterations of structural covariance, especially in bilateral cingulate and temporal lobes. Conclusions: There are alterations of brain volumetry and associated structural covariance within lobar regions in CSVD, which indicates the potential brain structural reorganization in CSVD.